Accounting Information, Digitalization, Intellectual Capital, and Stock Prices: The Moderating Role of CSR - Astrianto, Diego Maret; Lovita, Erna (Research of Accounting and Governance, 2026)
This study examines the effects of accounting information value relevance, digitalization disclosure, and intellectual capital on stock prices, with Corporate Social Responsibility (CSR) as a moderating variable. Using panel data from 17 Indonesian banking firms over 2021–2024 (68 firm-year observations), a fixed-effects regression model is employed to control for unobserved firm heterogeneity. The results indicate that earnings per share (EPS), price-to-book value (PBV), digitalization disclosure, and intellectual capital significantly influence stock prices (p < 0.05). Moderation analysis reveals that CSR strengthens the relationship between EPS and stock prices as well as between intellectual capital and stock prices, while the interaction effects of CSR with PBV and digitalization disclosure are not significant. These findings suggest that CSR does not uniformly enhance all value drivers. Model fit varies across specifications, highlighting the importance of robustness checks. Overall, the study shows that CSR enhances the market impact of profitability and intellectual resources, but not all accounting or digital signals. From a managerial perspective, firms should focus on sustaining high-quality earnings, developing intellectual capital, and integrating CSR strategically to improve market valuation.